Outcome of Corticosteroid Injection in Patients with Plantar Fasciitis - Naveed Gul, Abdul Munaf Saud, Tauseef Raza, Muhammad Afzal, Syed Abdur Rub Abidi, Yad Zamin Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Corticosteroid injection is frequently used for plantar heel pain (plantar fasciitis), although there is limited high-quality evidence to support this treatment. Objective: The purpose of this study is to determine the outcomes of corticosteroid injection in reducing the intensity of pain in patients with plantar fasciitis Methods: This descriptive study was conducted at Rawal Institute of Health Sciences –RIHS, Islamabad and comprised of 92 patients. After obtaining informed written consent from participants, demographic information such as age, gender, and body mass index (BMI) was collected. Each patient with plantar fasciitis who fulfilled the inclusion criteria had one intra-heel injection of triamcinolone and had two, six, and 12 week follow-up appointments in the outpatient department. The intervention's efficacy was assessed by measuring the amount of pain alleviation using the Visual Analogue Scale (VAS). Results: There were 59 (64.1%) male patients and 33 (35.9%) female among all cases. The mean age of the included cases was 35.23±12.67 years and the BMI was 26.8±14.35 kg/m2. 48 (52.2%) were married and 36 (39.1%) cases had urban residency. We found significantly reduction in pain score from baseline 5.72±4.24 to 1.03±2.11 with p value <0.005. Recurrence rate of pain was 2 (2.2%). Conclusion: We found that injecting steroid painkillers into the heel area of the foot not only significantly lessens plantar fasciitis pain, but also improves quality of life and cuts down on the frequency and intensity of painkiller use. Keywords: Corticosteroid, Pain, Vas, Plantar fasciitis